SENGKETA TENUREAL: REFLEKSI PERTENTANGAN SENTRALISME HAK MENGUASAI NEGARA DALAM UUPA DENGAN KEPENTINGAN MASYARAKAT ADAT (Sebuah Catatan Menuju Reformasi Hukum Agraria yang Pluralis) - Ahmad Basuki (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
Regulation of agrarian principles (UUPA) is one of traditional law product that is made to characteristic of agrarian colonial regulation into agrarian regulation that take place in accordance with the goal of Indonesian Republic. The regulation committee therefore underlines the importance of the rearrangement of ownership and exploitation agrarian resources. During the Orde Baru regime, The Right of Country control (HMM was mislead into power centralism several investors. Local community role and existence was disturbed. This,, no doubt. emerged so many tenureal dispute. To avoid such incident happening again. UUPA as an Umbrella Provision should be reformed into an accommodative agrarian regulation character which also ensure the local community interests.